Resurrection walk [compact disc, unabridged] - Connelly, Michael, 1956- (Connelly, Michael, 1956- Lincoln lawyer novel (Hachette Audio (Firm)), 2023)
Defense attorney Mickey Haller enlists Harry Bosch to help investigate the death of a deputy, blamed on the wife. But danger comes from those who covered up what the deputy's killing was really about.